ChemInform Abstract: Condensed‐Phase, Halogen‐Bonded CF3I and C2F5I Adducts for Perfluoroalkylation Reactions. Issue 31 (August 2015) - Sladojevich, Filippo; McNeill, Eric; Boergel, Jonas; Zheng, Shao‐Liang; Ritter, Tobias
Abstract Tetramethylguanidine and DMSO can be used to prepare the required adducts of type (I), (IX), and (XIV).